2001
DOI: 10.1614/0890-037x(2001)015[0075:eovtna]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Venturi-Type Nozzles and Application Volume on Postemergence Herbicide Efficacy1

Abstract: Field studies were conducted to compare venturi-type nozzles to a fan nozzle with respect to the efficacy of postemergence herbicides applied to common cocklebur and broadleaf signalgrass. Spray solutions of glufosinate, glyphosate, and paraquat were applied through all combinations of three nozzles and two application volumes. Venturi nozzles were a Delavan Raindrop Ultra (RU) and a Spraying Systems AI Teejet (AI). A Spraying Systems XR Teejet (XR) fan nozzle was included as a standard. Previous work indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 14 publications
6
58
0
Order By: Relevance
“…Control varies with herbicides, rates applied, and growth stage of weeds at the time of spraying. Nozzle types (Etheridge et al 2001;Mueller and Womac 1997), water quality (Buhler and Burnside 1983;de Villiers and du Toit 1993;Stahlman and Phillips 1979), and surfactants significantly affect herbicide efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Control varies with herbicides, rates applied, and growth stage of weeds at the time of spraying. Nozzle types (Etheridge et al 2001;Mueller and Womac 1997), water quality (Buhler and Burnside 1983;de Villiers and du Toit 1993;Stahlman and Phillips 1979), and surfactants significantly affect herbicide efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is not surprising that the effect of droplet size on herbicide efficacy appears to be dependent on species. In addition, the importance of adequate coverage, typically achieved with smaller droplets, has a more-consistent effect on the efficacy of contact herbicides, such as glufosinate (Etheridge et al 2001).…”
mentioning
confidence: 99%
“…In 56 % of studies examined by Knoche (1994), a decrease in the application volume rate led to an improvement or no effect on the efficacy of herbicides. This is consistent with other studies (McMullan 1995;Etheridge et al 2001;Ramsdale and Messersmith 2001), conducted after 1994. Changing the spray droplet size will impact the deposition, but the effect on coverage was not as correlated (Hanna et al 2009…”
Section: Introductionsupporting
confidence: 93%
“…Sikkema et al (2008) observed a reduction in Group A herbicide efficacies using DRT nozzles, but it should be pointed out that, that study only had one grass species (barnyardgrass, Echinochloa crus-galli (L.) P. Beauv) and only one type of DRT nozzle -this result was not observed in this study across nozzle or grass species. Results with paraquat, glyphosate, and imazamox plus imazapyr were consistent with Etheridge et al (2001), Wolf et al (2000), Messersmith (2001a, 2001b) and Sikkema et al (2008). DWRs with metribuzin were consistent with the results of Jensen et al (2001), though the photosystem II inhibitor used in that study was not metribuzin, but phenmedipham, which has a different site of action.…”
Section: Dry Weight Reductionssupporting
confidence: 71%
See 1 more Smart Citation